Features Of Kidney Damage at Patients with Ankylosing Spondiloarthritis (Texas Journal of Medical Science, 2021)
Kidney damage is a fairly common extra-articular manifestation of ankylosing spondiloarthritis (AS) and occurs with a frequency of 0.5 to 30% according to various clinical and epidemiological studies. However, the actual prevalence of renal disease in AS remains unspecified. This is largely due to the difficulties in verifying the diagnosis of "drug- nephropathy" in patients with a high level of comorbid pathology, in particular, arterial hypertension, metabolic syndrome and diabetes mellitus, which cause chronic kidney disease. The main causes of kidney damage directly related to AS are chronic autoimmune inflammation and drug-induced lesions associated with anti-inflammatory therapy. It has been proven that as the duration of AS increases, the incidence of CKD increases and this may be a hidden risk factor for an increase in mortality in these patients. In this context, the role of subclinical changes in the kidney is increasing, which may reflect the initial stages of CKD or precede it. The basis of the work was the results of a comprehensive clinical, instrumental and laboratory examination of 60 patients with AS